2018
DOI: 10.1038/s41559-018-0506-6
|View full text |Cite
|
Sign up to set email alerts
|

Translation of neutrally evolving peptides provides a basis for de novo gene evolution

Abstract: Accumulating evidence indicates that some protein-coding genes have originated de novo from previously non-coding genomic sequences. However, the processes underlying de novo gene birth are still enigmatic. In particular, the appearance of a new functional protein seems highly improbable unless there is already a pool of neutrally evolving peptides that are translated at significant levels and that can at some point acquire new functions. Here, we use deep ribosome-profiling sequencing data, together with prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
122
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 62 publications
9
122
1
Order By: Relevance
“…The conservation distribution of iORFs with translation signature (iORFsT1) is similar that of non-translated ones, suggesting that iORF retention is mainly guided by random mutations and genetic drift even when translated. The absence of selection signature is also consistent with the neutral evolution of most of intergenic polypeptides observed in rodents (Ruiz-Orera et al 2018), and with the weak effect of purifying selection acting on younger de novo genes in yeast, Drosophila and Arabidopsis (Carvunis et al 2012;Palmieri et al 2014;Zhao et al 2014;Li et al 2016;Vakirlis et al 2017). The resemblance to random sequences does not entirely preclude any potential molecular function and effect on fitness however because a recent study showed that a unneglectable fraction of expressed random sequences confers a positive effect on the fitness .…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The conservation distribution of iORFs with translation signature (iORFsT1) is similar that of non-translated ones, suggesting that iORF retention is mainly guided by random mutations and genetic drift even when translated. The absence of selection signature is also consistent with the neutral evolution of most of intergenic polypeptides observed in rodents (Ruiz-Orera et al 2018), and with the weak effect of purifying selection acting on younger de novo genes in yeast, Drosophila and Arabidopsis (Carvunis et al 2012;Palmieri et al 2014;Zhao et al 2014;Li et al 2016;Vakirlis et al 2017). The resemblance to random sequences does not entirely preclude any potential molecular function and effect on fitness however because a recent study showed that a unneglectable fraction of expressed random sequences confers a positive effect on the fitness .…”
Section: Discussionsupporting
confidence: 50%
“…The subsequent maintenance of the structure by purifying selection will lead to the gene being shared among species, as we see for groups of orthologous canonical genes. There are many ORFs associated with ribosomes in nonannotated regions, supporting their translation and the potential to produce de novo polypeptides which are the raw material necessary for de novo gene birth (Ingolia et al 2009;Wilson and Masel 2011;Carvunis et al 2012;Ruiz-Orera et al 2014;Lu et al 2017;Vakirlis et al 2017;Ruiz-Orera et al 2018). We distinguish de novo polypeptides, encoded by intergenic ORFs, from de novo genes because most of de novo polypeptides could be non-functional and seem to evolve neutrally (Ruiz-Orera et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over 500 million years of evolution from hydra to humans, the total number of ORFs have been thought to remain the same at around 30,000. With the advent of deep sequencing strategies in both genomics and proteomics fields, we are now discovering nORFs that have remained undiscovered or 'hidden' 1,2,5,6 . These nORFs are pervasive throughout the genome and are observed in both the coding and non coding regions 1,7 .…”
mentioning
confidence: 99%
“…Moreover, the lack of strong adaptation is not an 269 argument against evolutionary relevance. Neutrally evolving proteins have previously 270 been suggested to provide a basis for evolutionary novelty [29]. We suggest that 271 phenotypic mutations like TR are permissive.…”
mentioning
confidence: 85%
“…Phenotypic 27 mutations have been suggested to act as intermediate stepping stones for traits not yet 28 encoded on the DNA level [4]. In the context of two correlated point mutations, which 29 are jointly required for the formation of stabilising interactions in a protein, this has 30 lead to the formulation of "the look-ahead effect" [4]. Assuming only one of the two 31 point mutations are present on DNA level, and the second mutation is expressed by a 32 phenotypic mutation, the look-ahead effect hypothesis explores the probability of the 33 fixation of a novel phenotype prior to genotypic encoding.…”
mentioning
confidence: 99%